2001
DOI: 10.1038/sj.bjp.0704335
|View full text |Cite
|
Sign up to set email alerts
|

Release of non‐neuronal acetylcholine from the isolated human placenta is mediated by organic cation transporters

Abstract: 1 The release of acetylcholine was investigated in the human placenta villus, a useful model for the characterization of the non-neuronal cholinergic system. 2 Quinine, an inhibitor of organic cation transporters (OCT), reduced acetylcholine release in a reversible and concentration-dependent manner with an IC 50 value of 5 mM. The maximal e ect, inhibition by 99%, occurred at a concentration of 300 mM. 3 Procaine (100 mM), a sodium channel blocker, and vesamicol (10 mM), an inhibitor of the vesicular acetylch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 24 publications
2
93
0
Order By: Relevance
“…Instead, ACh appears to be synthesized and released when necessary, without storage. On the other hand, two polyspecific organic cation transporter subtypes, OCT1 and OCT3, are reportedly involved in the release of ACh in the human placenta (15) and in murine bronchial epithelium (16).…”
Section: -4 Vesicular Ach Transportermentioning
confidence: 99%
“…Instead, ACh appears to be synthesized and released when necessary, without storage. On the other hand, two polyspecific organic cation transporter subtypes, OCT1 and OCT3, are reportedly involved in the release of ACh in the human placenta (15) and in murine bronchial epithelium (16).…”
Section: -4 Vesicular Ach Transportermentioning
confidence: 99%
“…Not only did TEA and choline fail to inhibit the uptake of 4-Di-1-ASP, but ergothioneine-a specific substrate for OCTN1 [22]-also showed no inhibitory effects ( Figure 5C). Amiloride [6], MPP + [15], and agmatine [23], three other OCT inhibitors, likewise showed no significant inhibition of 4-Di-1-ASP uptake ( Figure 6). …”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Wessler et al studied the release of acetylcholine from placental villus and concluded that the process is mediated by OCT1 and OCT3 [6]. The expression of OCT2 in human placenta is reported by multiple authors [7][8][9][10] and refuted by others [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…OCT activity is modulated by a variety of drugs and endogenous compounds, such as monoamines and steroids. These agents can target the release of non-neuronal acetylcholine under physiological conditions and circulating catecholamines may also affect the release of non-neuronal acetylcholine (23).…”
Section: Discussionmentioning
confidence: 99%